2018
DOI: 10.1002/wsbm.1436
|View full text |Cite
|
Sign up to set email alerts
|

Committing the primordial germ cell: An updated molecular perspective

Abstract: The germ line is a crucial cell lineage that is distinct from somatic cells, and solely responsible for the trans-generational transmission of hereditary information in metazoan sexual reproduction. Primordial germ cells (PGCs)-the precursors to functional germ cells-are among the first cell types to be allocated in embryonic development, and this lineage commitment is a critical event in partitioning germ line and somatic tissues. Classically, mammalian PGC development has been largely informed by investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 108 publications
(233 reference statements)
2
12
1
Order By: Relevance
“…We also identified Endoderm-1 which may represent precursors of primitive and definitive endoderm. However, there are known differences between mouse and human in the formation of ExE cells (Shahbazi and Zernicka-Goetz, 2018) and PGC (Tan and Tee, 2019). Accordingly, we did not find similarities between mouse PGC and Endoderm-2, a cluster enriched in NANOS3, TFAP2C, and other primate PGC and hPGCLC markers.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…We also identified Endoderm-1 which may represent precursors of primitive and definitive endoderm. However, there are known differences between mouse and human in the formation of ExE cells (Shahbazi and Zernicka-Goetz, 2018) and PGC (Tan and Tee, 2019). Accordingly, we did not find similarities between mouse PGC and Endoderm-2, a cluster enriched in NANOS3, TFAP2C, and other primate PGC and hPGCLC markers.…”
Section: Discussioncontrasting
confidence: 80%
“…Interestingly, however, the Endoderm-2 cluster matched primarily with mouse epiblast cells despite showing resemblance to ExE ectoderm and ExE endoderm ( Figure 3I). We reasoned that the mismatch occurred because the Endoderm-2 cluster primarily contained hPGCLC, whose formation and gene expression diverge from mouse PGCs (Tan and Tee, 2019). A parallel comparison of our gastruloid data with hPGCLCs derived using in vitro human amnion model (Zheng et al, 2019), corroborated a strong correlation in gene expression between Endoderm-2 and hPGCLCs in that study ( Figure S3H).…”
Section: Gastruloids Contain Cells Similar In Gene Expression Profilesupporting
confidence: 70%
“…Interestingly however, cross-species comparison with mouse showed that the hPGCLC cluster had predicted labels of epiblast (64%), ExE ectoderm (13%), and ExE endoderm (10%; Figure 3I ). We reasoned the mismatch occurred because hPGCLC formation and gene expression diverge from mouse PGCs ( Tan and Tee, 2019 ). Accordingly, we found that the PGC module score, based on primate PGC predictors, of monkey PGCs was similar to that of gastruloid hPGCLCs but significantly higher than that of mouse PGCs (p<0.0001; Figure 5E ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, we found similarities between epiblast cell types, gastrulating cells (E-Gast and L-Gast1/2) to mouse PS and mesoderm, VE/YE to mouse ExE Endoderm, and TE to mouse ExE Ectoderm, suggesting conservation in the formation of these cell types. However, monkey E-PGCs were primarily predicted to correspond to mouse epiblast, PS, and nascent mesoderm than PGC, reflecting species differences in PGC formation ( Tan and Tee, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell treatment has been proposed as a potential intervention to improve endometrial quality and receptivity . However, the field is moving toward cell‐free therapies to improve safety and efficacy, making the function of endometrial‐derived EVs in improving embryo implantation potential described here an attractive future therapy to improve fertility and the success of IVF cycles in which implantation failure is a major limiting factor.…”
Section: Discussionmentioning
confidence: 99%